Development of A Bilingual Digital Booklet for Tourism In Malang City - Karlinda, Regina Dila; Karina Fefi Laksana Sakti; Tiksno Widyatmoko (Proceeding of International Conference on Education, Language, Literacies, and Literary Studies (ICONELS), 2025)
This research and development aimed to produce a bilingual digital booklet (Indonesia-Mandarin language) as a media for tourism information in Malang City aimed at tourists from China. This booklet is designed in the form of an e-book with an attractive appearance and equipped with images of tourist destinations, making it easier to convey information visually and interactively. The advantages of digital booklets compared to printed media are their durability, environmental friendliness, and ease of access via digital devices. The development process follows the five steps of the ADDIE model: analysis, design, development, implementation, and evaluation. Implementation was carried out by involving Chinese students from Guangxi Normal University and Chinese tourists through online testing. Validation was carried out by material and media experts, and for the results showed about product was suitable for use after revision. This digital booklet not only helps Chinese tourists get to know tourist destinations in Malang City, but can also be used by local tourists thanks to the presentation of information in two languages.